Rethinking Orality I Codification, Transcodification and Transmission of 'Cultural Messages' - Ercolani, Andrea; Lulli, Laura (Transcodification: Arts, Languages and Media, 2022)
The volume deals with the mechanisms of the oral communication in the ancient Greek culture. It focuses on the 'cultural message' of the texts, considered under two perspectives: the methodologies of cognitivism, and ethology, to analyze its embrional manifestations, and the tools of historical and literary analysis, to highlight the codification of the cultural message, and its evolutions in the changes of the communication system.